2005
DOI: 10.1007/s10979-005-7370-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Cues to Deception vs. Topic Incriminating Potential in Criminal Confessions.

Abstract: Coding statements of criminal suspects facilitated tests of four hypotheses about differences between behavioral cues to deception and the incriminating potential (IP) of the topic. Information from criminal investigations corroborated the veracity of 337 brief utterances from 28 videotaped confessions. A four-point rating of topic IP measured the degree of potential threat per utterance. Cues discriminating true vs. false comprised word/phrase repeats, speech disfluency spikes, nonverbal overdone, and protrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
2
31
1
Order By: Relevance
“…Whether someone is intentionally lying or not is rarely a key issue in clinical contexts, but deception cues are related in complex ways to stress cues (Davis, Walters, Vorus, & Connors, 2000;Davis, Markus, Walters, Vorus, & Connors, 2005) which are a concern of clinicians. Also, judgment processes found in deception detection may apply to other types of clinical judgment.…”
Section: Decoding Versus Encoding Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether someone is intentionally lying or not is rarely a key issue in clinical contexts, but deception cues are related in complex ways to stress cues (Davis, Walters, Vorus, & Connors, 2000;Davis, Markus, Walters, Vorus, & Connors, 2005) which are a concern of clinicians. Also, judgment processes found in deception detection may apply to other types of clinical judgment.…”
Section: Decoding Versus Encoding Studiesmentioning
confidence: 99%
“…It is possible to verify brief descriptions of events or actions given during a high stakes interview such as a criminal confession. It is also possible to identify behavioral cues to lying in these short utterances, and to distinguish these cues from verbal and nonverbal cues to stress that occur as the topic gets hotter, whether the person lies about it or not (Davis et al, 2005). In contrast, it is difficult to independently validate the authenticity of brief clinical states in a dance/movement therapy session in order to compare that information with judgments by clinicians.…”
Section: Decoding Versus Encoding Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in their meta-analysis of cues to deception, DePaulo et al (2003) found that strong motivation to succeed in the lie, and lies about transgressions, factors more likely to be present in high stakes situations, emerged as important moderating factors in the elicitation of prominent cues to deception. Indeed, the small body of existing research investigating real life, high stakes lies, has produced some promising results, and suggests that there may be some useful cues to deception that are more likely to emerge in high stakes situations; for example, an increase in speech dysfluency (Davis, Markus, Walters, Vorus & Connors, 2005;Vrij & Mann, 2001a), and equivocal language (Adams & Jarvis, 2006;Wright Whelan, Wagstaff & Wheatcroft 2013).…”
mentioning
confidence: 99%